Therapeutic challenges in central nervous system viral infections: advancing mesenchymal stem cell-based strategies for treating neuroinflammation and promoting tissue repair - Carbone-Schellman, Javier; Fontecilla-Escobar, Javiera; Sales-Salinas, Nicolás; Chaparro-Pico, William F.; Molina-Berríos, Alfredo; Ruete, María Celeste; González, Pablo A.; Machuca, Mayra A.; Opazo, Ma. Cecilia; Ezquer, Marcelo E.; Duarte, Luisa F. (Frontiers in Immunology, 2025)
Although significant progress has been made in medicine and antimicrobial research, viral infections continue to pose a critical global health challenge, particularly when they involve the central nervous system (CNS). Despite advances in vaccines, antiviral agents, and small molecule therapeutics, current strategies remain insufficient to address the complex consequences of many CNS infections fully. Notably, many viruses are neurotropic and can invade the CNS, triggering infectious neuroinflammation that often lead to chronic neurological disorders and lasting morbidity. Current therapeutic approaches are largely ineffective in preventing or reversing this long-term neurological damage, underscoring the urgent need for innovative prophylactic and therapeutic interventions. Mesenchymal stem cells (MSCs) have emerged as a promising strategy to counteract chronic neuroinflammation and promote tissue repair following viral CNS infections. This review provides a comprehensive overview of CNS viral infection and neuroinflammation, including epidemiology and pathophysiology, and critically examines the limitations of existing treatments, particularly their inability to mitigate persistent neurological sequelae. Furthermore, we summarize recent preclinical and clinical studies investigating the use of MSCs in the context of CNS viral infections, highlighting their immunomodulatory and neuroprotective mechanisms, and discuss the challenges and future directions for MSC-based therapies in clinical settings.